Golden Inspirations: using Motivational Videos to make a Positive Difference in the Lives of Seniors - Ali, Sonila; Shah, Ibrahim; Memon, Samreen; Ara, Anjum (Riviera Publishing, 2023)
In the current era, the advent of digital media has significantly altered how individuals establish connections and seek sources of inspiration. Inside this context, a noteworthy avenue arises known as